GFRP bar-reinforced seawater sea-sand concrete beam under the combined influence of seawater exposure and sustained load: Durability and degradation mechanism. (September 2022) - Chang, Yufei; Wang, Yanlei; Li, Bingnan; Wang, Mifeng; Zhou, Zhi; Ou, Jinping
Abstract: This paper presents an experimental study on the durability of the seawater sea-sand concrete (SWSSC) beam reinforced with glass fiber-reinforced polymer (GFRP) bars under the combined influence of seawater exposure and sustained load. The effects of exposure duration (90, 180, and 270 days) and sustained load level (25 % and 40 % of ultimate load) on the beam's durability were investigated. The results indicated that the combined influence of seawater exposure and sustained load had little effect on the initial stiffness of the load vs mid-span deflection curve, but it influenced the second stiffness of the curve. The ultimate load improved slightly with the increased sustained load level in the early time due to the further hydration of SWSSC and the water swelling of bars. Then it was reduced with the exposure duration and sustained load level. The degradation mechanism of the GFRP bar-reinforced SWSSC beam under the combined influence of seawater exposure and sustained load was revealed: the composite action loss of SWSSC and GFRP bar is chiefly responsible for the beam degradation in seawater; the internal stress induced by the sustained load could facilitate the development of the existing damages and accelerate the beam degradation.